Analysis of Different Treatment Methods for Breast Cancer - Zhang, Taisen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This research discusses the mechanisms of current medical treatments for breast cancer and a brief analysis of the treatments. The aim of this research is to present the different cancer therapies and to select the most promising and promising therapies for breast cancer based on the performance of each therapy, where chemotherapy, radiotherapy, and immunotherapy for breast cancer are discussed. By analyzing the various therapies, it is concluded that all three therapies selected for discussion have shown a significant increase in efficacy over their traditional counterparts, but at the same time, the risks and potential shortcomings of the newer therapies have been demonstrated in experimental trials. Through the analysis of this research, it is hoped that there will be a combination of techniques and breakthroughs in therapies for breast cancer. Each therapy has its own shortcomings, and the combination of chemotherapy, radiation, and immunotherapy with current cancer therapies will be the future of cancer breakthroughs.